Domestic burns that occurred during the COVID-19 pandemic in Brazil: a descriptive cross-sectional study - Pan, Raquel; Santos, Paola Maria Freitas dos; Resende, Isabella Luiz; Nascimento, Kleiton Gonçalves do; Adorno, José; Cunha, Marco Túlio Rodrigues da; Freitas, Noélle de Oliveira (São Paulo Medical Journal, 2023)
BACKGROUND: Due to “stay at home” restrictions during the coronavirus disease 2019 (COVID-19) pan-demic, people spent more time at home leading to an increase in home accidents, including burns. OBJECTIVE: To investigate the epidemiology of burns that occurred within homes during the COVID-19 pandemic in Brazil. DESIGN AND SETTINGS: This was a quantitative, descriptive, and cross-sectional study with a non-prob-abilistic sample. METHODS: Data were collected through the distribution of survey links on social networking sites and websites, and through email between December 2020 and February 2021. Participants were over 18 years of age, living in Brazil. Data analysis was performed using descriptive and dispersion statistics. RESULTS: A total of 939 adults (aged > 18 years) participated in this study. The mean age was 37.2 years (standard deviation [SD] = 12.5), 75.6% were female, 70.0% self-reported white skin color, 74% had com-pleted higher education, and 28.1% had an income of 3 to 6 times the monthly minimum wage. A total of 21.6% suffered burns during the pandemic, 44.3% from a hot object. Approximately 49.3% never had access to a burn prevention campaign. CONCLUSION: It is necessary to develop burn prevention strategies that reach a wider population and to strengthen public policies to reduce the prevalence of domestic burns, especially during the pandemic.